Neuroepidemiology study of headache in the region of Jammu of north Indian population: A cross-sectional study - Sudershan, Amrit; Pushap, Agar Chander; Younis, Mohd; Sudershan, Srishty; Bhagat, Sheetal; Kumar, Hardeep; Panjalyia, Rakesh K.; Kumar, Parvinder (Frontiers in Neurology, 2023)
Background: Headache disorders represent a major public health problem globally. It is more in developing countries with the rising trends in young adults affecting negatively their quality of life. There has been very little information on the epidemiology of headache disorder in the Jammu division of the north Indian population. Aim: The present study is aimed to find out the prevalence of headache and its two major types i.e., migraine and TTH (Tension-Type Headache) in the population of Jammu division. Methods: The study was conducted in two phases: (Phase I: Face-face interview and Phase II: E-based sampling) and sufferers of headaches were incorporated into the study based on the ICHD-3 criteria for a representative sample. Frequency distribution and mean ± standard deviation were used in descriptive statistics to describe the data sets, while a t-test, chi-square test, multiple logistic regression, and prevalence ratio were used in inferential statistics. Results: A total of 3,148 patients were recruited, with an overall prevalence of headache of 53.84%, with a female majority (38.18%) over males 15.66%. Regarding the type, migraine was found to be highly prevalent (33.25%) type than TTH (20.58%). Females suffering from migraine showed the highest prevalence (25.28%) in contrast to females suffering from TTH (12.89%). Socio-demographic variables such as gender (female) (AOR=2.46, 95% CI [2.12-2.85], p-value <0.0001) and marital status (married) (AOR: 1.46, 95% CI [1.11-1.92] p-value=0.006) showed a significant association with the headache. Conclusion: The prevalence of headache is high in the Jammu division of J&K India with migraine being the high prevalent type.